Integrated Briefcase Model: A Teaching Aid in the Practicum of Digital Electronics - Mashoedah Mashoedah; Umi Rochayati; Muhammad Munir (JOURNAL OF EDUCATION, 2013)
This study is aimed at designing as well as producing  an integrated briefcase  model  as  a  teaching  aid  in  the  teaching  of  digital  electronics practicum  and  its feasibility.   This study  can  be  classified  as  research  and development study. It was conducted in the Electronics Engineering Education Department and State  Vocational School 2 Yogyakarta. The teaching aid was developed  through: conducting  needs analysis,  designing,  implementing,  and testing.  The  testing  was  carried  out  twice  covering  the performance   and feasibility.  The data were collected by using questionaires  distributed  to the users.  The students  of SMK Negeri 2  Yogyakarta were the   subjects  of  the research. In this study the data were analyzed  descriptively. The study findings showed  that  the  teaching  aid  could  be  realized  and  meet  the  competence required in the digital electronics subject. The score obtained from  the content validity test was 90% (categorized as very feasible).  The score of the material validity was 80% (categorized as feasible).  The score of the feasibility  in terms of the material aspect was 42% (categorized as feasible).  The technical aspect was scored 69.83% (categorized as feasible).